AN ANALYSIS OF TEACHER PERFORMANCE APPRAISALS AND THEIR INFLUENCE ON TEACHER PERFORMANCE IN SECONDARY SCHOOLS IN KENYA - Kagema, Josphat; Irungu, Cecilia (UPI Press, 2018)
Every organization has an objective towards optimum performance and the employees are the key drivers in achieving that. It is necessary therefore that the employeesâ€™ performance reach optimality for the success of the organization which is a primary goal of every organization including learning institutions. The present research investigated the influence of teacher performance appraisals on teacher performance in secondary schools in Kenya. Employing stratified and simple random sampling methods, 46 secondary schools with 460 teachers in two counties in Kenya were taken as samples. Â The variables under research included teacher remuneration, government policies, school administration, the school environment, and the school curriculum, which were under investigation in form of comparisons, explanations, and relationships on the aspects of teacher motivation to perform well. The research found that teacher appraisals influenced teacher performance. In general, the teachers perceived that government policies are unfavorable to them in terms of career advancement and introduction of the policies in place. The paper concludes with recommendations on application of the appraisal system to motivate teachers and thereby improve the performance of learners.